Efektivitas Promosi Online Melalui Instagram Terhadap Keputusan Pembelian Pada Akun @Goodstore.Magelang - Alfian Nasrullah; Siti Mudhi Khatul Fata; Sekar Ayuning Kasih (CV. ITTC INDONESIA, 2022)
Social media that has many users is Instagram. Instagram is a social media that is often used by individuals and companies to share information, build relationships with clients, and build brands. This study aims to determine the effectiveness of Instagram online promotions on purchasing decisions on the @goodstore.magelang account. This type of research is descriptive with quantitative methods with a sample or respondents of 100 people. The results of the data correlation test study between the effectiveness of online promotions and purchase decisions amounted to 1,000 with a significant value of 0,000. Based on this, the relationship between the effectiveness of online promotion and the purchase decision is included in a very strong correlation.